Can Automated Agents Proficiently Negotiate with Humans? - RAZ LIN; KRAUS, SARIT (Communications of the ACM, 2010)
The article discusses research into the design of computer programs which can conduct negotiations. An overview of the challenges involved in designing a negotiator advanced enough to be capable of negotiating successfully with humans is presented. Examples of various programs which have achieved some of the necessary benchmarks are discussed, such as Diplomat, Colored-Trails, and QOAgent. The strategies used by the designers of these programs are analyzed. These include randomization to simulate non-deterministic behavior, a mechanism for making concessions, and a database to store acquired information.